Dorsal Translation of Ulnar Head after the Arthroscopic Wafer Procedure for Ulnar Impaction Syndrome - Yun, Keonhee; Jung, Ki Jin; Nho, Jae-Hwi; Cho, WhiJe; Kim, Byung Sung (Archives of Hand and Microsurgery, 2019)
Purpose: The purpose of this study was to evaluate the results of the arthroscopic wafer procedure (AWP) for ulnar im-paction syndrome (UIS) and identify preoperative factors and degree of distal radioulnar joint (DRUJ) translation that could assist in predicting outcomes. Methods: We retrospectively reviewed the medical records of 9 patients (11 wrists) who underwent AWP for UIS. Among these, 5 cases were converted to secondary ulnar shortening osteotomy and were categorized to group A and the remaining 6 cases were categorized to group B. The ulnar variance (UV), radioulnar ratio (RUR) by computed tomog-raphy or magnetic resonance imaging (MRI), MRI evidence of mechanical impaction in the ulnar or lunate, grip power, Disability of Shoulder, Arm and Hand (DASH) score, and Mayo wrist score were examined before and after AWP. Results: The MRI evidence did not differ significantly between groups A and B (p>0.05). The average UV and RUR changed from 1.6±0.7 mm and 0.68±0.17 before AWP to –1.5±0.9 mm and 0.54±0.10 after AWP, respectively. The differ-ence between the preoperative RUR (0.65) and postoperative RUR in group B (0.49) was significant (p=0.027, Pearson correlation coefficient=0.862). The grip strength, DASH score, and Mayo wrist score improved from 77.1%, 47.6, and 69.1 to 85.2%, 16.8, and 85.5, respectively. Conclusion: If patients have persisting pain and DRUJ dorsal translation is not reduced after wafer procedure, secondary ulnar shortening osteotom may be required. KCI Citation Count: 0